Protective effects of a probiotic-fermented germinated grain complex on neurotransmitters and sleep quality in sleep-deprived mice - Cheng, Jiahua; Wu, Qiqi; Sun, Rui; Li, Wujuan; Wang, Zhuoling; Zhou, Min; Yang, Tian; Wang, Jing; Lyu, Yuhong; Yue, Changwu (Frontiers in Microbiology, 2024)
Objective To explore the effects of probiotic fermentation products of germinated grains on cognitive and sleep improvement in mice with sleep deprivation induced by chlorophenylalanine (PCPA), and to provide theoretical and experimental basis for the development of natural products to alleviate insomnia. Methods ELISA and high-performance liquid chromatography (HPLC) were used to determine the contents of γ-aminobutyric acid and L-theanine in fermentation products. Open Field Test was used to analyze the changes of emotional behavior between groups before and after intervention. ELISA was used to analyze the changes of hypothalamic serotonin, GABA, glutamate, and serum interleukin 6. 16S rRNA sequencing was used to analyze the changes of intestinal flora before and after the intervention of compound fermentation products. LC–MS/MS was used to analyze the changes of intestinal SCFAs before and after the intervention. Results The content of GABA and L-theanine in 7 L fermentation products was 12.555 μmol/L (1.295 mg/L) and 0.471 mg/mL by ELISA. Compared with the PCPA-induced Model group, the sleep duration of the KEY group was statistically significant (p < 0.0001). Compared with the PCPA-induced Model group, the number of crossing the central lattice in the KEY group was significantly increased, and the number of grooming was significantly reduced (all p < 0.05), suggesting that the anxiety behavior of the mice was improved. In addition, this study found that the compound fermentation products could significantly increase the content of neurotransmitters such as 5-HT, GABA and Glu in the hypothalamus of mice, reduce the content of inflammatory factors such as IL-6, IL-1β and TNF-α in serum, regulate the structure of intestinal flora and increase the content of short-chain fatty acids. Conclusion Probiotic fermentation products of germinated grains can significantly improve sleep deprivation in PCPA mice, which may be related to regulating the levels of neurotransmitters and inflammatory factors, improving the structure of intestinal flora, and increasing the content of short-chain fatty acids. This study provides new candidates and research directions for the development of natural drugs to alleviate insomnia.